2017
DOI: 10.2147/ott.s118151
|View full text |Cite
|
Sign up to set email alerts
|

TCF21 functions as a tumor suppressor in colorectal cancer through inactivation of PI3K/AKT signaling

Abstract: Colorectal cancer (CRC) has become a major public health problem, ranking as the third most common type of cancer. Our previous study has revealed that TCF21 is frequently silenced by promoter hypermethylation in both CRC cell lines and primary CRC, with TCF21 methylation being significantly correlated with lymph node invasion. In this study, we further analyze the expression of TCF21 in CRC tissues and investigate the role of TCF21 in CRC in vitro and in vivo. We also explore the possible pathway regulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
(30 reference statements)
2
25
0
12
Order By: Relevance
“…The study carried out by Tan et al reported that enforced expression of TCF21 could reduce the proliferation and migration of HCC cells and enhance apoptosis in vitro [15]. Dai et al revealed that TCF21 might inhibit tumor progression in colorectal cancer through suppressing PI3K/AKT signaling pathway [24]. Besides, two published studies have demonstrated that the down-regulation of TCF21 could inactivate metastasis suppressor KISS1, thus leading to cancer metastasis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The study carried out by Tan et al reported that enforced expression of TCF21 could reduce the proliferation and migration of HCC cells and enhance apoptosis in vitro [15]. Dai et al revealed that TCF21 might inhibit tumor progression in colorectal cancer through suppressing PI3K/AKT signaling pathway [24]. Besides, two published studies have demonstrated that the down-regulation of TCF21 could inactivate metastasis suppressor KISS1, thus leading to cancer metastasis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Low TCF21 expression has been shown to be related to high-grade or invasive–aggressive cancers with lymph node or distant metastases indicating recurrence and with an inferior prognosis. 24 , 26 TCF21 may thus serve as an excellent diagnostic or prognostic biomarker predicting poor outcome, as demonstrated in gastric cancer, 25 melanoma, 29 colorectal cancer, 39 and lung cancer cases. 38 , 40 Aberrant methylation of TCF21 can be detected not only in solid cancer tissues but also in sputum and urine samples from cancer patients.…”
Section: Regulation Of Tcf21 Expressionmentioning
confidence: 99%
“…A recent study confirmed that upregulation of TCF21 significantly increased the expression of KISS1 and decreased the expression of phosphatidylinositol 3-hydroxy kinase (PI3K) and phosphorylated AKT, indicating inactivation of PI3K/AKT signaling. 39 In addition, overexpression of TCF21 also inhibited the expression of matrix metalloproteinase (MMP)-2 and MMP-9, which are involved in cancer cell invasion and metastasis. 39 Similarly, Wei et al 28 demonstrated that TCF21 inhibited MMP-2 and MMP-10 and decreased ovarian cancer cell invasion.…”
Section: Tumor Suppressive Signatures Of Tcf21mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increase in CDH1 expression might be a possible reason for decreased migration of TCF21 ‐expressing 786‐O cells in the current study, through alternative downstream transcriptional pathways, because we did not detect changes in the extracellular epitope for CDH1 (Canel et al ., ; Onder et al ., ). Furthermore, our results that overexpression of TCF21 inhibits migration are in accordance with in vitro studies in colorectal cancer cell lines (Dai et al ., , ) as well as siRNA suppression of endogenous TCF21 in renal progenitor cells which increased migration (Plotkin and Mudunuri, ). Although re‐expression of TCF21 in melanoma cells and Caki‐1 ccRCC cells has been described to activate expression of the metastatic suppressor KISS1 (Arab et al ., ; Zhang et al ., ), in the current study KISS1 expression does not seem to be involved in the suppressed migration of 786‐O cells transfected with TCF21 .…”
Section: Discussionmentioning
confidence: 99%